New Public Service In Bandung Through The Concept Of Smart City - Syahirul Alim; Arie Kumala Nisa; Abdul Hair (Journal of Politics and Policy, 2019)
New Public Service is a paradigm of governance that prioritizes public services in a democratic, fair and equitable manner. Bandung City Government should provide good public services along with the development of the current digital era. Smart City is one way for the Bandung City Government to organize its government. The results of this study indicate that the public services of the city of Bandung are carried out in various ways such as providing services to the community easily through applications, wifi parks, online complaint services, official websites, e-budgeting, and so on.Keywords: New Public Service, Smart City, Bandung